Tiktok Shop as a Social Commerce Platform in Indonesia: a Prisma-Based Systematic Literature Review - Marita Sri Nuryati; Arianis Chan; Tetty Herawaty (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: The rapid development of technology and the internet has significantly transformed business marketing practices. TikTok has emerged as a rapidly growing digital marketing platform in Indonesia, which currently holds the position as the country with the second-largest TikTok user population in the world. This phenomenon highlights the platform’s substantial potential as a new medium for marketing activities.Purpose: This study aims to examine the role of TikTok as an emerging digital marketing platform in Indonesia and to synthesize existing research findings on how the platform influences consumer engagement, purchasing behavior, and marketing effectiveness.Design/methodology/approach: This research employs a Systematic Literature Review (SLR) using the PRISMA approach. Numerous relevant scientific journals were identified and analyzed as secondary data sources to answer research questions related to the use of TikTok as an emerging marketing platform.Findings/Result: The findings indicate that TikTok functions as an interactive digital marketing platform where short-form content, algorithm-driven recommendations, and social interaction mechanisms significantly enhance consumer engagement. These features act as marketing stimuli that influence consumer responses, including purchase intention, brand awareness, and brand loyalty. The findings also support the Stimulus Organism Response (S-O-R) theoretical framework, suggesting that digital content and platform interactions shape consumer perceptions and behavioral responses in social commerce environments.Conclusion: Overall, TikTok demonstrates significant potential as an effective digital marketing platform in Indonesia by facilitating interactive communication, enhancing consumer engagement, and supporting brand visibility. However, the effectiveness of TikTok marketing strategies depends on the strategic use of platform features, content creativity, and the digital capabilities of business actors.Originality/value: This study contributes to the understanding of TikTok’s role as a new marketing medium in Indonesia. By synthesizing findings from various scientific publications using the PRISMA-based SLR method, the research provides comprehensive insights into how TikTok can be optimized for brand communication and digital marketing strategies. Keywords: tiktok, digital marketing, engagement, brand image, systematic literature review